Therapeutic alliance dimensions and dropout in a therapeutic community: "Bond with me and I will stay" - Janeiro, Luis (2018)
Purpose - A better therapeutic alliance at the beginning of treatment for addictive behaviours has been found to prevent dropout. The purpose of this paper is to evaluate how the development of therapeutic alliance dimensions was associated with the dropout prevention.Design/methodology/approach - A total of 23 participants presented a substance use disorder related to heroin or cocaine and were in three distinct treatment phases of a therapeutic community. Each participant filled in the therapeutic alliance measures once a week after mini-groups. A naturalistic prospective research design was used to collate 198 repeated alliance measures.Findings - Participants who presented stable bond development at higher levels tended to stay in treatment, whereas those who developed stable bonds at lower levels tended to drop out. The goals and tasks dimension increased significantly across the phases and was not associated with dropout.Practical implications - To prevent dropout, therapists should pay special attention to residents who manifest difficulties in establishing stable and secure bonds and not overestimate the impact of the goals and tasks alliance dimension, as it is not a failsafe indicator of treatment retention.Originality/value - The alliance dimensions were differentiated (bond, goals and tasks) and studied throughout the treatment, pointing out the importance of therapeutic relationship dynamic variables to prevent dropout.